Decision-Making of Swiss Farmers and the Role of the Veterinarian in Reducing Antimicrobial Use on Dairy Farms - Gerber, Manuela; Dürr, Salome; Bodmer, Michèle (Frontiers in Veterinary Science, 2020)
The aim of this study was to investigate dairy farmers’ motivation to reduce antimicrobial use on their farms. Furthermore, factors influencing dairy farmers’ decision-making regarding dairy cow health are identified and the role of the farm veterinarian in these processes characterized. A customized structured questionnaire was sent to all participants (n=59) of a current antimicrobial reduction project among dairy farmers in the Canton of Fribourg, Switzerland, by mail. Fifty-eight completed questionnaires were returned and evaluated (response rate 98.3%). The majority of respondents were men (n=56, 96.6%) and farm managers (n=55, 96.5%) managing their farms as their main occupation (n=56, 98.2%). On a 5-point-Likert-scale the factors "My veterinarian is putting pressure on us to use less antimicrobials" (median=2.5, interquartilerange=1-3) and "Other farmers also reduce antimicrobial use" (2, 1-3) were the least important factors concerning motivation of farmers to reduce the use of antimicrobials in dairy cows. The veterinarian (4, 4-5), as well as the own intuition (4, 3-4) were the two factors with significantly stronger influence on the decision making of farmers regarding dairy cow management than the remaining factors. Colleagues, other experts such as nutritionists, and family members had a significantly lower influence on decision-making. In general, the farmers surveyed are satisfied with the quality of the consultancy given by the veterinarians (4, 4-5). They understand recommendations provided by the private veterinarians (4, 3.75-4) and they feel understood by the veterinarians (4, 3-4). However, only 26% (n=14) of the surveyed farmers were willing to pay for good quality, farm-adapted consulting offered by their veterinarian. The veterinarian is by far the most important person influencing the farmer in his decision-making concerning animal health and treatment. Unfortunately, the private veterinarian is on the other hand one of the least motivating factors for antimicrobial reduction. Swiss veterinarians should be aware of their influence on their farmers' decisions and more clearly promote antimicrobial reduction.